ANALISIS EKSERGI PADA UNIT DISTILASI ATMOSFERIK DAN VAKUM MINYAK BUMI - Zikri, Ahmad (Politeknik Negeri Sriwijaya, 2014)
The atmospheric and vacuum distillations are the first plant in a crude oil refinery, in which several intermediate product are obtained through distillation of the crude oil mixture. To increase the thermodynamic efficiency, we need to use both the temperature-enthalpy and exergy losses together. It is important to determine the exergy losses profiles and to analyze the distribution losses in all stage of distillation column. Aspen Plus software is used as assistance to simulate changes in the given circumstances. The results of the exergy and exergoeconomic analyses are presented in this paper. The important unit in this analysis are distillation column operating conditions, crude heating furnace, and supporting Heat Exchanger. In this study, atmospheric and vacuum distillation columns at refineries UP-III-Plaju Indonesia become the case study. The proposed method is to condition the feed temperature limits vary with the quality of the resulting products were unchanged. The fuel requirement would be decreased, as well as the temperature which is result by crude heating furnace. In atmospheric distillation column, about 0.6 % (0.25 T/D) and 20.8 % (8.9 T/D) for vacuum distillation is direct fuel can be derived. With this analysis we can save operating cost approximately 1.4 million U.S. per year.